Perancangan Sistem Informasi Penjualan Di Toko Mini Moni Snack Berbasis Website - Tiara Aulia Nur Fadilla; Riyan Abdul Aziz; Safarina Binashrillah; Serly Rindayanti; Vita Ariska (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
. In the era of technology and information that is increasingly developing, the internet is starting to become a necessity for all circles of the general public who are inherent and have become their daily needs. Business via the internet is a business in which the process of both ordering, payment and delivery is through online media or the internet. The purpose of this study is to design a website at the Mini Moni Snack Shop as a media promotion and service to customers. The website can be accessed by all ages including internet users. The system development method uses the RAD (Rapid Application Development) method which tends to be more structured. In designing this website it uses the programming language PHP version 7 and Phpmyadmin as the database. The conclusion from this research is that with a website-based sales system, of course, it can make it easier to make sales transactions.